2005
DOI: 10.1111/j.1540-8167.2005.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Long‐Lasting Persistent Atrial Fibrillation: Critical Structures for Termination

Abstract: Termination of persistent AF can be achieved in 87% of patients by catheter ablation. Ablation of the structures annexed to the left atrium-the left atrial appendage, coronary sinus, and PVs-have the greatest impact on the prolongation of AF cycle length, the conversion of AF to atrial tachycardia, and the termination of focal atrial tachycardias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
564
3
16

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 613 publications
(599 citation statements)
references
References 58 publications
16
564
3
16
Order By: Relevance
“…However, inconsistency in the ablation technique and technology, different definitions of success and arrhythmia recurrence and differences and limitations in the methods of clinical follow-up after the procedure complicate the realistic appreciation of the results and, therefore, it is not surprising that significant differences in outcome of AF ablation exist in the published series [3]. Besides that, the long term outcome data after ablation of AF are still scarce and limited to period of only 3-8 emphasizes the importance of creating irreversible ablative lesion in the first procedure [25,28,29,47]. Indeed, the inability to create permanent and continuous ablative lesions in the first procedure represents one of the principal limits of the actual ablation technology.…”
Section: Figure 2 Catheter Ablation Of Paroxysmal Af: Elimination Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…However, inconsistency in the ablation technique and technology, different definitions of success and arrhythmia recurrence and differences and limitations in the methods of clinical follow-up after the procedure complicate the realistic appreciation of the results and, therefore, it is not surprising that significant differences in outcome of AF ablation exist in the published series [3]. Besides that, the long term outcome data after ablation of AF are still scarce and limited to period of only 3-8 emphasizes the importance of creating irreversible ablative lesion in the first procedure [25,28,29,47]. Indeed, the inability to create permanent and continuous ablative lesions in the first procedure represents one of the principal limits of the actual ablation technology.…”
Section: Figure 2 Catheter Ablation Of Paroxysmal Af: Elimination Ofmentioning
confidence: 99%
“…It is considered that artery occlusion was mediated by direct thermal injury of its wall with edema or spasm and/or cumulative injury from previous procedure. In complex AF procedures, ablation of substrate is not limited to the LA [25]. It has been shown that RF ablation of cavo-tricuspid isthmus could be accompanied by temporary but significant reduction of fractional flow reserve (FFR) in 21.2% of patients, or rarely by acute occlusion of distal segment of right coronary artery with inferior myocardial infarction [188,189].…”
Section: Thromboembolic Complications Preprocedural Thrombosis Tranmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Sometimes lesions may need to be delivered within the CS in order to achieve block although this may not always be necessary to terminate the flutter. 7,18,19 Lesions extending from septal MA to the right inferior PV may also achieve flutter termination but these are more difficult to deliver both on account of difficulty in catheter deployment in this area and the relatively longer extent as compared with the In rare instances involving reentry around the veins, following PV isolation additional lesions extending from right PVs to the fossa or left PVs to the appendage and / or the MA may be required to terminate the arrhythmia. 7,18 In instances where one or more of the above macroreentrant circuit is suspected but not confirmed (changing tachycardias, disorganization to AF or organization to sinus rhythm during entrainment), a combination of the above lesion sets can be empirically deployed.…”
Section: Macroreentrant Flutter Circuitsmentioning
confidence: 99%